BRIDGING PERSPECTIVES: HOW LECTURERS AND STUDENTS DEFINE EFFECTIVE ESP TEACHING (ENGLISH FOR HOSPITALITY) IN HIGHER VOCATIONAL EDUCATION - Irmawati, Dini Kurnia (Faculty of Administrative Science, Universitas Brawijaya, 2025)
This study seeks to examine the perspectives of lecturers and students in higher vocational education about effective English for Specific Purposes (ESP) instruction within the hospitality context. A sequential explanatory mixed-method design was utilized. In the initial phase, questionnaire data were gathered from 60 hotel management students and examined through descriptive statistics to discern perceptual patterns. During the second phase, semi-structured interviews were conducted with 3 ESP lecturers to enhance the quantitative findings. The findings show that informants concur on the significance of establishing explicit learning objectives, employing diverse interactive pedagogical techniques, and incorporating activities that emphasize speaking skills. They concur that evaluations must align with course objectives. However, challenges remain in promoting active student inquiry and in the clear incorporation of cognitive, emotional, and psychomotor domains. The research indicates that successful ESP training in vocational contexts is complex and dependent on the alignment of instructional design, classroom execution, and professional relevance. Future investigations are advised to use diverse vocational schools and larger participant samples to enhance generalizability. Longitudinal studies are also recommended to examine the impact of ESP classroom learning on workplace performance. Further research should examine the perspectives of industry stakeholders to improve the alignment between education and professional demands.